The clothing shopping behaviour of young females before, during and after the COVID-19 pandemic in Gauteng - Jacobs, B.M. (Bertha Margaretha) (University of Pretoria, 2024)
Dissertation (Msc(Consumer Science Clothing Management))--University of Pretoria, 2024.